Effect of Different Feed Restriction Regimes During the Starter Stage on Productivity and Carcass Characteristics of Male and Female Ross 308 Broiler Chickens - Novel, D.J.; Ngambi, J.W.; Norris, D.; Mbajiorgu, C.A. (International Journal of Poultry Science, 2008)
An experiment was conducted to determine the effect of different feed restriction regimes during the starter stage (14-21 days) on productivity and carcass characteristics of male and female Ross 308 chickens. A 3 (feeding levels: ad-libitum intake, 50% ad-libitum intake and 75% ad-libitum intake) x 2 (male and female chickens) factorial arrangement in a complete randomized design was used. Feed restriction affected (p